2010
DOI: 10.1159/000321354
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular Determinants of Cognitive Decline and Brain Volume Change in Elderly Patients with Type 2 Diabetes

Abstract: Background/Aims: The present study examined the relationship between microvascular complications and cognitive decline and the development of structural brain abnormalities over a period of 4 years in patients with type 2 diabetes mellitus (T2DM). Methods: Sixty-eight elderly patients with T2DM had 2 cognitive assessments with a 4-year interval. Two MRI scans, performed at the same time as the cognitive assessments, were available from 55 patients. Changes in cognitive performance over time were expressed as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
68
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 33 publications
2
68
0
1
Order By: Relevance
“…Albuminuria, a marker of chronic vascular kidney disease, is associated with accelerated cognitive decline in diabetic patients [2]. Cerebromicrovascular disease manifests as impaired vasoreactivity [7, 8], hypoperfusion and decreased metabolism that may lead to hypoxia and brain tissue loss [9-12].…”
Section: Introductionmentioning
confidence: 99%
“…Albuminuria, a marker of chronic vascular kidney disease, is associated with accelerated cognitive decline in diabetic patients [2]. Cerebromicrovascular disease manifests as impaired vasoreactivity [7, 8], hypoperfusion and decreased metabolism that may lead to hypoxia and brain tissue loss [9-12].…”
Section: Introductionmentioning
confidence: 99%
“…Also the study by de bresser et al examining the relationship between microvascular complications and cognitive decline and the development of structural brain abnormalities in Diabetics, reported that presence of albuminuria predicted accelerated cognitive decline in Type2 diabetes (P<0.001). (17) In our study, 10.7% already had Diabetic Retinopathy when they were diagnosed with Diabetes or developed it within six months. This prevalence of Diabetic Retinopathy in our study on newly diagnosed diabetics is somewhat similar to that of a study by Abdollahi et al in 2006, where the prevalence reported was 13.4%.…”
Section: Discussionmentioning
confidence: 48%
“…In that regard, it is important that a significant association between serum ADMA level and slower gait speed was demonstrated among elderly individuals (Obayashi et al 2016). Type 2 diabetes mellitus (Duarte et al 2015) also leads to neurovascular dysfunction, which is associated with increased risk for brain function loss and long-term cognitive impairment (Biessels and Reijmer 2014;Brundel et al 2012Brundel et al , 2014de Bresser et al 2010;Palta et al 2014;Reijmer et al 2011;Ruis et al 2009;Ryan et al 2014Ryan et al , 2016van den Berg et al 2008van den Berg et al , 2009van den Berg et al , 2010. Increased oxidative stress and heightened inflammation associated with cardiovascular risk factors may also affect arachidonic acid metabolism, decreasing production of vasodilator prostaglandins and EETs and/or increasing synthesis of vasoconstrictor eicosanoids, such as 20-hydroxyeicosatetraenoic acid (20-HETE), contributing to neurovascular dysfunction.…”
Section: Discussionmentioning
confidence: 99%